Gestational Exposure to Air Pollution Alters Cortical Volume, Microglial Morphology, and Microglia-Neuron Interactions in a Sex-Specific Manner - Bolton, Jessica L.; Marinero, Steven; Hassanzadeh, Tania; Natesan, Divya; Le, Dominic; Belliveau, Christine; Mason, S. N.; Auten, Richard L.; Bilbo, Staci D. (Frontiers in Synaptic Neuroscience, 2017)
Microglia are the resident immune cells of the brain, important for normal neural development in addition to host defense in response to inflammatory stimuli. Air pollution is one of the most pervasive and harmful environmental toxicants in the modern world, and several large scale epidemiological studies have recently linked prenatal air pollution exposure with an increased risk of neurodevelopmental disorders such as autism spectrum disorder (ASD). Diesel exhaust particles (DEP) are a primary toxic component of air pollution, and markedly activate microglia in vitro and in vivo in adult rodents. We have demonstrated that prenatal exposure to DEP in mice, i.e., to the pregnant dams throughout gestation, results in a persistent vulnerability to behavioral deficits in adult offspring, especially in males, which is intriguing given the greater incidence of ASD in males to females (~4:1). Moreover, there is a striking upregulation of toll-like receptor (TLR) 4 gene expression within the brains of the same mice, and this expression is primarily in microglia. Here we explored the impact of gestational exposure to DEP or vehicle (VEH) on microglial morphology in the developing brains of male and female mice. DEP exposure increased inflammatory cytokine protein and altered the morphology of microglia, consistent with activation or a delay in maturation, only within the embryonic brains of male mice; and these effects were dependent on TLR4. DEP exposure also increased cortical volume at embryonic day (E)18, which switched to decreased volume by postnatal day (P)30 in males, suggesting an impact on the developing neural stem cell niche. Consistent with this hypothesis, we found increased microglial-neuronal interactions in male offspring that received DEP compared to all other groups. Taken together, these data suggest a mechanism by which prenatal exposure to environmental toxins may affect microglial development and long-term function, and thereby contribute to the risk of neurodevelopmental disorders.